Urgensi Implementasi Doktrin Business Judgment Rule Dalam Peraturan Pemerintah Nomor 3 Tahun 2019 Tentang Investasi Pemerintah - Muhammad Husein Haekal; Suparji Suparji; Yusuf Hidayat (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2023)
The business judgment rule is a legal principle of the common law legal system which aims to provide protection to the board of directors in carrying out their duties as decision-makers in the company from being legally responsible if the decision turns out to be detrimental to the company. The new paradigm of government investment in Government Regulation No. 63 of 2019 On Government Investment which adopts the principle of business judgment rule in Law No. 40 of 2007 On Limited Liability Companies aims to mitigate the risk of actions or decisions in government investments that can cause state losses. This study aims to analyze the urgency of applying the doctrine of business judgment rule in government investment governance based on Government Investment Regulations The application of the business judgment rule doctrine in the supervision authority of the Government Investment Committee (KIP) and the operational authority of the Government Investment Operator (OIP) was found to be one of the answers to what legal protection is regulated in Government Investment PP to KIP and OIP in this study, which was carried out using the normative legal research method. In order to provide OIP and KIP, to the parties involved in the implementation of government investment, with legal protection, the business judgment rule doctrine, which was previously outlined in the Company Law, will be applied to Government Investment PP arrangements. So that assuming that there is a decline in the worth of the venture so it can't be ordered as an activity that can make misfortunes the state, insofar as KIP and OIP have completed their obligations sincerely, as per and in accordance with the arrangements of regulations and guidelines, and have given many advantages to the public interest.Keywords: Business Judgment Rule; Government Investment Abstrak Business judgment rule merupakan doktrin yang mengajarkan bahwa keputusan direksi mengenai aktivitas perseroan tidak dapat langsung dipersalahkan oleh siapa pun meski keputusan tersebut merugikan perseroan. Paradigma baru investasi pemerintah dalam Peraturan Pemerintah Nomor 63 Tahun 2019 tentang Investasi Pemerintah yang mengadopsi pengaturan doktrin business judgment rule dalam Undang Undang Nomor 40 tahun 2007 tentang Perseroan Terbatas bertujuan untuk mengurangi risiko tindakan dan/atau keputusan dalam aktivitas investasi pemerintah yang dapat mengakibatkan kerugian negara. Penelitian ini bertujuan untuk menganalisis urgensi penerapan doktrin business judgment rule dalam tata kelola investasi pemerintah berdasarkan PP Nomor 3 Tahun 2019 tentang Investasi Pemerintah. Penelitian ini dilakukan dengan metode penelitian hukum normatif, yang di dalamnya ditemukan bahwa diterapkannya doktrin business judgment rule dalam kewenangan supervisi pada Komite Investasi Pemerintah (KIP) dan kewenangan operasional pada Operator Investasi Pemerintah (OIP) adalah salah satu jawaban atas perlindungan hukum yang diatur dalam PP Investasi Pemerintah untuk KIP maupun OIP. Penerapan doktrin business judgement rule yang sebelumnya telah diatur di dalam UUPT dan diadopsi ke dalam PP Investasi Pemerintah bertujuan untuk memberikan perlindungan hukum bagi pihak-pihak terkait dalam pelaksanaan investasi pemerintah, yang dalam hal ini OIP dan KIP. Sehingga apabila terjadi penurunan nilai investasi, tidak langsung dapat dikategorikan sebagai tindakan yang dapat menimbulkan kerugian negara, sepanjang KIP maupun OIP telah melakukan tugas dengan itikad baik, sesuai dan sejalan dengan ketentuan peraturan perundangan, dan telah memberikan banyak kemanfaatan bagi kepentingan umum.Kata Kunci: business judgment rule; investasi pemerintah